Pengembangan Lembar Kerja Peserta Didik Berbasis Kemampuan Penalaran Matematis dengan Mind Mapping - Husein Adikalan, Naufal; Imamah AH, Nurul; Suryaningrum, Christine Wulandari (Universitas Islam Jember, 2024)
The purpose of this research is to develop a Students' Working Sheet (LKPD) based on mathematical reasoning for 7th-grade students of UPTD SPF Junior High School 3 Bondowoso. In this study, Thiagarajan's development model (1974) is used, which consists of four stages: Define, Design, Develop, and Disseminate. However, the development of mind mapping-based LKPD is only limited to 3D. The initial observation shows that students have different levels of mathematical reasoning ability. The result of the study includes the validity, practicality, efficiency, and effectiveness of the LKPD. After being validated by two validators, the validity of LKPD is assessed, with 3,25 as the average score which indicates a good level of validity. The practicality of the LKPD was assessed by the teacher's questionnaire, which received 81,25% as the average score, which shows that the LKPD can be considered practical. The efficiency of the LKPD was assessed by the student’s questionnaire, which received 86,27%, which shows that the LKPD can be considered as efficient. Keywords: Students' Working Sheet, mathematical reasoning, mind mapping